Molecular distributed sensors using dark soliton array trapping tools - Sorayut Glomglome; Somsak Mitatha; Preecha P. Yupapin (My University, 2011)
We present the novel system of molecular distributed sensors using dark soliton pulse array, whereas the multi dark soliton sources can be generated and the molecular distributed sensors presented via an optical multiplexer (MUX). Initially, the dark soliton array with different center wavelengths can be generated, then the transmission molecules/atoms can be secured by using the dark soliton behaviors, whereas the dark soliton valley can be configured as the molecule/atom trapping potential well, which can be used to trap molecule/atom. In this case, the transported molecules/atoms in the router can be used to form the molecular distributed sensors, whereas the induced changes in the molecular distributed sensors can be formed and measured via the drop port of each output multiplexer.
Keywords: Trap (plumbing); Mechanical and Optical Resonators